Implementation of OTP Code as Application Login Verification Via Whatsapp - Nasution, Adnan Buyung; Hrp, Ahir Yugo Nugroho; Yudi, Yudi; Fauzi, Muhammad (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
Application security is a major concern in the development of information systems today. One of the common methods used to improve security is two-factor verification using One Time Password (OTP). This study proposes and implements a login verification system using OTP sent via WhatsApp. This method not only takes advantage of WhatsApp's popularity as a broad communication platform, but also ensures that users receive verification codes directly on their mobile devices. The implementation is carried out using the latest technology in web-based application development, with a focus on user security and convenience. The results of this study are expected to provide practical guidance for developers to integrate more secure and efficient login verification into their applications.